2019
DOI: 10.1159/000499693
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1-, but not Growth and Differentiation Factor 15-, Receptor Activation Increases the Number of Interleukin-6-Expressing Cells in the External Lateral Parabrachial Nucleus

Abstract: List of non-standard abbreviations CGRP-calcitonin gene related peptide Ex4-exendin-4 GDF15-growth and differentiation factor 15 GFRAL-GDNF family receptor alpha-like GLP-1-glucagon like peptide 1 GLP-1R-glucagon like peptide 1 receptor IL-6Rα-interleukin-6 receptor alpha MIC1-macrophage inhibitory cytokine 1 NTS-nucleus of the solitary tract PBN-parabrachial nucleus PBNel-external lateral parabrachial nucleus RFP-red fluorescent protein STAT3-signal transducer and activator of transcription 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The mKATE2 reporter staining reflects IL‐6 expression, as supported by mKATE2 staining being co‐localised with IL‐6 mRNA, which was identified by RNAscope. Moreover, the mKATE2 reporter staining co‐localised with the staining obtained by an anti‐IL‐6 antibody, which, as shown by ourselves (see Supporting information, Figure S1), as well in previous studies,by others demonstrated less staining in different strains of IL‐6 gene knockout mice…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The mKATE2 reporter staining reflects IL‐6 expression, as supported by mKATE2 staining being co‐localised with IL‐6 mRNA, which was identified by RNAscope. Moreover, the mKATE2 reporter staining co‐localised with the staining obtained by an anti‐IL‐6 antibody, which, as shown by ourselves (see Supporting information, Figure S1), as well in previous studies,by others demonstrated less staining in different strains of IL‐6 gene knockout mice…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we used RedIL6, an IL‐6 reporter mouse that was described recently . Briefly, the RedI6 reporter mouse was generated according to a gene knock‐in protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential role for cytokine signaling in the transduction of anorectic GLP-1 signals has also been suggested. Co-localization of interleukin-6 (IL-6) and GLP1R+ cells has been detected in the hypothalamus, brainstem, and the lateral parabrachial nucleus, and administration of exendin-4 increased the proportion of IL-6+ cells in the external parabrachial nucleus [ 26 ]. Acute intracerebroventricular (ICV) injection of exendin-4 also increased the expression of IL-6 in the brainstem, and of IL-6 and IL-1β in the rat hypothalamus.…”
Section: How Important Is Gut-derived Glp-1 For the Control Of Food I...mentioning
confidence: 99%